2009
DOI: 10.1111/j.1365-2109.2009.02283.x
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol prevents oxidative damage, inhibits oxygen radical generation and increases antioxidant enzyme activities of juvenile Jian carp (Cyprinus carpiovar. Jian)

Abstract: This study was conducted to evaluate the e¡ects of dietary myo-inositol (MI) on the antioxidant status of juvenile Jian carp (Cyprinus carpio var. Jian). A total of 1050 Jian carp (22.28 AE 0.07 g) were randomly distributed into seven groups of three replicates each, feeding diets containing graded levels of MI (163.5, 232.7, 384.2, 535.8, 687.3, 838.8 and 990.3 mg kg À 1 diet) for 60 days. Results indicated that the malondialdehyde content was the lowest for ¢sh fed diets containing ! 384.2 mg MI kg À 1 , an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…The contents of malondialdehyde (MDA), protein carbonyl (PC) and reduced glutathione (GSH) in the gill were determined according to the procedures described by Zhang et al [48], Baltacıoglu et al [49], and Vardi et al [50], respectively. The anti-superoxide anion (ASA) (O 2 À -scavenging ability), anti-hydroxy radical (AHR) (OH -scavenging ability) and CAT activities were measured as described by Jiang et al [51]. The total SOD, CuZnSOD and GPx activities were assayed as described by Jin et al [52], Jiang et al [53] and Zhang et al [48], respectively.…”
Section: Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of malondialdehyde (MDA), protein carbonyl (PC) and reduced glutathione (GSH) in the gill were determined according to the procedures described by Zhang et al [48], Baltacıoglu et al [49], and Vardi et al [50], respectively. The anti-superoxide anion (ASA) (O 2 À -scavenging ability), anti-hydroxy radical (AHR) (OH -scavenging ability) and CAT activities were measured as described by Jiang et al [51]. The total SOD, CuZnSOD and GPx activities were assayed as described by Jin et al [52], Jiang et al [53] and Zhang et al [48], respectively.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…In fish, the superoxide radical and hydroxyl radical were the primary free radicals that induce oxidative damage [81]. Jiang et al [51] reported that the ASA and AHR were able to minimize the ROS through scavenging superoxide and hydroxyl radicals, respectively. In this study, riboflavin deficiency significantly decreased AHR and ASA capacity, and supplemented with optimal riboflavin reversed this decrease in the gills of young grass carp ( Table 5), indicating that riboflavin deficiency increased ROS production may be partly through decreasing free radicals scavenging capacity in the gills of fish.…”
Section: 4mentioning
confidence: 99%
“…Glutathione peroxidase (GPx) activities were assayed as previously described [48]. The CAT activities were measured as described in our previous study [50]. The assay mixture consisted of 100 mM KPO 4 buffer (pH 7.0), 10 mM H 2 O 2 and 50 mL of intestinal homogenates in a total volume of 1 mL.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…The contents of malondialdehyde (MDA), protein carbonyl (PC) and reduced glutathione (GSH) in the intestine were determined according to the procedures described by Zhang et al [35], Baltacıo glu et al [36] and Vardi et al [37], respectively. The CAT activity was measured as described by Jiang et al [38]. The CuZnSOD and GPx activities were assayed as described by Jiang et al [39] and Zhang et al [35], respectively.…”
Section: Biochemical Analysismentioning
confidence: 99%